2021
DOI: 10.1038/s41598-021-98320-1
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and characterisation of endothelial cells from patients with chronic thromboembolic pulmonary hypertension

Abstract: Pulmonary endarterectomy (PEA) resected material offers a unique opportunity to develop an in vitro endothelial cell model of chronic thromboembolic pulmonary hypertension (CTEPH). We aimed to comprehensively analyze the endothelial function, molecular signature, and mitochondrial profile of CTEPH-derived endothelial cells to better understand the pathophysiological mechanisms of endothelial dysfunction behind CTEPH, and to identify potential novel targets for the prevention and treatment of the disease. Isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Additionally, our sample size is limited, and these results should be verified in a bigger patient group. Future work will aim to expand in PAH-EC, our recent results in oxygen consumption and mitochondrial functionality in CTEPH-EC, where we found an increased mitochondrial respiration activity in all the respiratory chain complexes compared to HPAEC 37 . Additionally , we aim to study the metabolism of pulmonary artery smooth muscle cells (PASMCs) of both diseases.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, our sample size is limited, and these results should be verified in a bigger patient group. Future work will aim to expand in PAH-EC, our recent results in oxygen consumption and mitochondrial functionality in CTEPH-EC, where we found an increased mitochondrial respiration activity in all the respiratory chain complexes compared to HPAEC 37 . Additionally , we aim to study the metabolism of pulmonary artery smooth muscle cells (PASMCs) of both diseases.…”
Section: Discussionmentioning
confidence: 72%
“…tive potential but reduced angiogenic capacity is a true feature of ECs or whether this is secondary to limitations of in vitro assays where ECs are neither exposed to the paracrine signaling nor experiencing biomechanical forces from the pulmonary ECM. To determine the effects of support cells and biochemical forces on PH are hyperproliferative, with increased migration but reduced angiogenic capacity on standard angiogenesis assays (25,26). However, how these ECs are affected by other pulmonary cell types and paracrine ligand/receptor signaling remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CTEPH-derived endothelial cells (CTEPH-EC) presented a significant increase in oxidative stress levels, specifically mtROS production, and reduced expression of SOD-2 compared to healthy human pulmonary artery ECs used as control cells [41]. Nukala et al also showed that CTEPH-EC exhibited an increase in intracellular ROS, advanced oxidation protein products and total protein carbonyl content (PCO), and a downregulation of GPX4 and GPX1 proteins, demonstrating dysregulation of the oxidative stress response and highlighting the involvement of oxidative stress in CTEPH [42].…”
Section: Oxidative Stress In Cteph (Group IV Ph)mentioning
confidence: 99%